Buying and Selling Online in View of Islamic Law - Hermawan, Risdianto; Aerin, Wafa (Islamic Studies Journal, 2023)
The development of technology and communication is so fast, penetrated into all aspects of life, not least also in business or trade. Buying and selling online is currently much loved by people in Indonesia, even the world. Online buying and selling system is a system that works for transactions (exchange of goods and services) that produce selling value that is done online. This system is much loved because people do not need to bother going to the seller to buy the desired item without limited space and time. Islam itself views online buying and selling as one of the tools in economic activity. However, there are many assumptions in the community about the law of buying and selling according to the view of Islamic law. There are criteria for allowing and prohibiting buying and selling according to Islamic views, as well as in the case of buying and selling done online.